1999
DOI: 10.1080/01140671.1999.9514082
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethanol on climacteric senescence in five cultivars of carnation

Abstract: The effects of ethanol on carnation (Dianthus caryophyllus L.) cut flowers were studied by treating five cultivars ('Yellow Candy', 'Sandrosa', 'Francisco', 'White Candy', and 'Iury') with up to 8% ethanol solution and measuring vase life, solution uptake, delay in bud opening of flowers, and ethylene production. Treatment with 4 or 6% ethanol increased the vase life of 'Yellow Candy', 'White Candy', and 'Iury', but not of 'Sandrosa' or 'Francisco'. Cultivars showed variable response to ethanol treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
(17 reference statements)
2
6
0
Order By: Relevance
“…Succinic acid was applied at the same concentrations as malic acid. Concentrations of ethanol (0, 2 and 4% v/v) were chosen based on previously obtained results Pun et al 1999). All the above chemicals were applied at preservative solutions.…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Succinic acid was applied at the same concentrations as malic acid. Concentrations of ethanol (0, 2 and 4% v/v) were chosen based on previously obtained results Pun et al 1999). All the above chemicals were applied at preservative solutions.…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
“…This presumably ensured more carbohydrates that were available for petal metabolism leading to an increase in vase life . Pun et al (1999) used 1, 2, 4, 6 and 8% ethanol for preservation of five carnations cultivars and found a difference in response of cultivars to ethylene and thus applied ethanol. They assumed that it depends on differences in levels of ethylene production and carbohydrate reserves.…”
Section: Introductionmentioning
confidence: 99%
“…They also mentioned that treatment with 4% ethanol inhibited ethylene production as well as sensitivity to ethylene and responsive to ethanol. The effectiveness of ethanol in extending vase life correlated closely with the longevity, ethylene production and ethylene sensitivity [2] . Longevity of vase life is an important factor in consumer preference and considerable research has been carried out on the causes of carnation senescence [3,6].…”
Section: Introductionmentioning
confidence: 78%
“…It has been reported that bougainvillea bracteoles were attractive at the end of 6-day observation period and dropped 32.2% with treated the STS (0.5 oz/Gallon) while, 100% was dropped in control tree. [2] It has been reported that treatment with 4 and 6% ethanol increased the vase life of' carnation flowers and cultivars showed variable response to ethanol treatment with regards to vase life increment and delay in bud opening. They also mentioned that treatment with 4% ethanol inhibited ethylene production as well as sensitivity to ethylene and responsive to ethanol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation